PENDEKATAN TRANSDISIPLIN SEBAGAI BENTUK INTEGRASI ILMU - Rahmah Rahmah (PT. Saha Kreasi Indonesia, 2025)
Transdisciplinary approaches have emerged as a response to the growing complexity of global issues that cannot be adequately explained through a single disciplinary lens. This model positions scientific inquiry as a collaborative space in which boundaries between fields are crossed, allowing concepts, methods, and values from diverse domains to interact and complement one another. By integrating academic knowledge, local wisdom, and practical experience, transdisciplinarity fosters more comprehensive understandings and generates solutions that are both innovative and applicable. Consequently, this approach has become central to discussions on the theoretical foundations of transdisciplinarity, its methodological processes, and its relevance to contemporary societal needs. Findings from recent studies indicate that transdisciplinarity is not merely a methodological choice, but a transformative paradigm that promotes more adaptive, inclusive, and synergistic forms of scientific collaboration.